Robust Predictor-Based Control of Uncertain Linear Systems with Delay via Integral Sliding Mode Control*. Issue 1 (July 2017) - Loukianov, A.G.; Caballero-Barragán, H.; Osuna-Ibarra, L. P; Plestan, F.
Abstract: In this paper, a continuous control strategy for robust stabilization of a class of uncertain multivariable linear systems with delays in both the state and control variables is proposed. A predictor is designed to compensate the delay effect in control input, and then an integral sliding mode control technique along with super-twisting algorithm is applied to compensate partially the effect of the perturbation term. Finally, a nominal delay-free part of the control input is designed to stabilize the sliding mode dynamics. The method is extended to the class of systems modeled in Regular form, it is proposed a transformation for the systems with delay in state then results in a system delay-free in state. Conditions for the stability of the closed-loop uncertain system are derived. Simulation results are presented and compared against previous works.